PERCEPTIONS OF URBAN LANDSCAPE: A STUDY OF COGNITIVE MAPPING IN AIN BEIDA, ALGERIA - Bekri Narimane; Mazouz Said (International Journal of Innovative Technologies in Social Science, 2024)
The urban landscape of Algerian cities features a mix of traditional and contemporary architectural forms, offering a diverse range of experiences and perspectives. The heterogeneous nature of this terrain motivated us to investigate the cognitive representation of this scenery in the minds of the inhabitants of Ain Beida. The study emphasizes the cognitive map, which manifests as visual representations, such as drawings or images, as well as sensory experiences and memories that are gathered and stored over a period of time. The perception of this mental image varies among individuals and locations. We conducted a comprehensive analysis of the existing literature to precisely identify the category under investigation and select a suitable approach for evaluating, comprehending, and interpreting the urban landscape of the above-mentioned city. An iconographic was employed as a research instrument selected to carry out a comprehensive survey with a sample of the population encompassing various socio-professional groups, with a primary focus on urban stakeholders such as architects, urban planners, and elected officials. The findings revealed a diverse range of mental maps, indicating the unique perspectives of each interviewee on their city.